Characterization of soil structure in Neuras, a Namibian desert-vineyard - Eden, Marie; Bens, Oliver; Betz, Sarah; Völkel, Jörg (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
Soil plays an important role in the context of vine growth and wine production; particularly soil structure which governs plant water uptake. Therefore, soil physical and hydrological properties were studied at Neuras vineyard, located near the Namib Desert. Water is scarce in this environment and wine production is limited to few vineyards in Namibia, overall. Managed plots and unmanaged nearby sites were investigated using field and laboratory methods. Viticultural techniques were noted and management related aspects were gathered in an interview. Datasets from two sampling trips in 2014 and 2016 were generated. In 2014, older vineyard soils displayed different properties than unmanaged soils or a younger vineyard, showing lower bulk densities and higher total porosities, with increased organic carbon and nitrogen contents. In 2016, the unmanaged reference plot differed from managed plots mainly in terms of lower electrical conductivity and higher cation exchange capacity. In managed soils contents of Smectites and Vermiculites were higher, while those of Chlorites and Illites were lower. Soil water retention properties were also altered, in line with structural changes indicated by bulk density and total porosity. These differences were more pronounced in vineyards of different ages than in those with even ages and indicate overall very different soil and soil structural conditions for the older versus the younger vineyards affecting vine growth.